MORPHOLOGICAL AND SYNTACTICAL ERRORS OF JUNIOR HIGH SCHOOL STUDENTS WITH DIFFERENT SEX IN SPEECH PRODUCTION - Zaniar, Savira -; Afandi, Mujad Didien; Authar, Nailul; Djuwari, Djuwari; Pramudita, Niken Ayu (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
There are differing opinions in the field of cognitive sciences when it comes to the role of sex in language acquisition. Men and women exhibit differences in their speaking and writing ability as a result of their distinct social roles throughout evolution. These disparities are equally, if not more, evident in students, both during normal and abnormal growth. In addition to the well-documented advantage that girls have in early language development, it is noteworthy that the majority of developmental problems that predominantly impact communication, speech, and language skills are more prevalent in boys. This article seeks to elucidate the disparities between sex regarding ordinary communication and language development, as well as the disparities in the occurrence of neurodevelopmental disorders connected to communication. Additionally, particular attention is given to data derived from the field of neuroscience, which may offer valuable insights into the neurological mechanisms that contribute to the comprehension of this event. We contend that the structural arrangement of the female brain confers women with an innate edge in developing communication and language systems compared to men. Divergent perspectives are present on the differentiation between sex within the field of cognitive sciences. The talks are founded upon clinical, social, and political perspectives. The evolutionary and biological perspectives have often emphasized arguments related to 'nature', whereas feminist and constructivist viewpoints have often emphasized arguments related to 'nurture' when discussing cognitive sex differences. This narrative review provides a comprehensive analysis of the origins and historical evolution of these arguments, as well as a summary of the findings in the field of sexually polymorphic cognition. By adopting multidisciplinary techniques, we aim to highlight the importance of interconnecting disciplines and gaining a more comprehensive knowledge of the precise factors that contribute to sex differences and gender diversity in cognitive capacities.